(3bQI GdYjhf Ydi GdLhgQ Gdecfhfs - (3Ydj Hf Ydj GdYRi GdeGdcj GdeNddGJjs; (3GdYRj , Ydj Hf Ydj GdYRj, GdeNddGJj,J (B981 (3g` ? s ((3YHO GdQMef Hf eMeO Hf YGeQ GdCNVQj , J (B- 983 (3g`s)
(3ChdgG (B:s
(3hHYO abO WdH efi Cf CLYd TQMkG Ydi efXheI ai GdeYGfi hGdHjGf s
(3BNQgG (B:s
(3hLYd ef GdQMjb GdeNJhe ZHhJg Je s
(3hQO GdYfhGf GdCUdi ai GjVGM Gdecfhf (B1/ 384s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GdTGQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs